Silent meningioma leading to death - Bhattacharya, P; Chattopadhyay, S (Nepal Journal of Medical Sciences, 2014)
Benign intracranial meningiomas are seldom the cause of death in elderly.It may be the triggering factor for a sequence of events which may ultimately lead to death. The silent nature of such tumors leads to delay in diagnosis and thus proper management. Findings at autopsy may confirm the diagnosis and cause of death in such cases. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 72-73 DOI: http://dx.doi.org/10.3126/njms.v3i1.10364